2015
DOI: 10.1144/geochem2013-245
|View full text |Cite
|
Sign up to set email alerts
|

Recent Lithuanian peri-urban ombrotrophic bog records: indices derived from the contents of lead, zinc, copper and nickel

Abstract: Two Lithuanian c . 50-cm long peat cores from ombrotrophic bogs were analysed, namely, Rėkyva near Šiauliai and Žudiškės near Vilnius. Ash content, bulk density, chemical element concentrations determined by EDXRF and 210 Pb dating by gamma spectrometric methods were used. Geochemical data of deep Rėkyva peatland mine layers, dated by 14 C to the BC/AD boundary, enable the estimation of reference values for the calculation of increase coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Due to selective absorption, chemical elements enter the plant in favorable proportions for life [8][9][10]. This is especially evident in various plant organs, where chemical elements have their specific function.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to selective absorption, chemical elements enter the plant in favorable proportions for life [8][9][10]. This is especially evident in various plant organs, where chemical elements have their specific function.…”
Section: Resultsmentioning
confidence: 99%
“…The content of heavy metals in the explored soils was determined on the KFK-3 device by a photocolorimetric dithizone method by G.Ya. Rin'kis's recipe [6][7][8][9][10]. The reproducibility of the method was equal to ± 4.2%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…soil with high organic matter content is not a textural class [19]. We studied only minerogenic soil, since peaty or organic soil needs separate research, as it may be greatly influenced by anthropogenic pollution, as shown in the study of peri-urban ombrotrophic bog records [42].…”
Section: Why Were Such Aims and Tasks Chosen?mentioning
confidence: 99%
“…An information about the content of toxic ingredients in the soil of a particular region take a very important place at solving majority practical environmental problems of anthropogenic pollution [1][2][3][4][5][6]. At pollution level assessment as background usually take uncontaminated territories with a similar soil cover for which concentration of heavy metals is known [7,8].…”
Section: Introductionmentioning
confidence: 99%